2016
DOI: 10.1007/s11145-016-9699-8
|View full text |Cite
|
Sign up to set email alerts
|

Early literacy and comprehension skills in children learning English as an additional language and monolingual children with language weaknesses

Abstract: Many children learning English as an additional language (EAL) show reading comprehension difficulties despite adequate decoding. However, the relationship between early language and reading comprehension in this group is not fully understood. The language and literacy skills of 80 children learning English from diverse language backgrounds and 80 monolingual English-speaking peers with language weaknesses were assessed at school entry (mean age = 4 years, 7 months) and after 2 years of schooling in the UK (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 60 publications
1
21
1
1
Order By: Relevance
“…It is currently unclear whether the relations between oral language and reading comprehension are comparable for EL1 and EAL learners, which may in turn influence the developmental trajectories in reading comprehension over time (Farnia & Geva, 2013). The few studies that compared the pattern and strength of these relations between the first-language and second-language learners have reported mixed findings (e.g., Babayiğit, 2014Babayiğit, , 2015Bowyer-Crane, Fricke, Schaefer, Lervåg, & Hulme, 2017;Lesaux, Lipka, & Siegel, 2006;Trapman, van Gelderen, van Steensel, van Schooten, & Hulstijn, 2014;van Gelderen et al, 2003). For example, Trapman et al (2014) found that whereas receptive vocabulary, grammar and metacognition were strong predictors of reading comprehension in bilingual Dutch-speaking students, word reading fluency was the strongest predictor of monolingual reading comprehension.…”
Section: Comparisons Of Oral Language and Text Comprehension Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is currently unclear whether the relations between oral language and reading comprehension are comparable for EL1 and EAL learners, which may in turn influence the developmental trajectories in reading comprehension over time (Farnia & Geva, 2013). The few studies that compared the pattern and strength of these relations between the first-language and second-language learners have reported mixed findings (e.g., Babayiğit, 2014Babayiğit, , 2015Bowyer-Crane, Fricke, Schaefer, Lervåg, & Hulme, 2017;Lesaux, Lipka, & Siegel, 2006;Trapman, van Gelderen, van Steensel, van Schooten, & Hulstijn, 2014;van Gelderen et al, 2003). For example, Trapman et al (2014) found that whereas receptive vocabulary, grammar and metacognition were strong predictors of reading comprehension in bilingual Dutch-speaking students, word reading fluency was the strongest predictor of monolingual reading comprehension.…”
Section: Comparisons Of Oral Language and Text Comprehension Relationmentioning
confidence: 99%
“…However, against this broad picture, the findings from individual studies vary considerably. Some have reported that second-language learners catch up with (Farnia & Geva, 2011, 2013 or even outperform their monolingual peers on word reading (Bowyer-Crane et al, 2017;Burgoyne, Whiteley, & Hutchinson, 2010) even during the early primary grades. Likewise, some have found no second-language disadvantage in reading comprehension (Lesaux, Rupp, & Siegel, 2007;Lesaux & Siegel, 2003).…”
Section: Comparison Of El1 and Eal Learners' English Oral Language Anmentioning
confidence: 99%
“…This was not replicated, however, in a later study by Babayiğit ( 2015 ), in which no structural differences between monolingual and bilingual readers were found. Similarly, Bowyer-Crane et al ( 2016 ) found no differences in the predictors of L1 and L2 reading comprehension when they compared second-grade bilingual children to monolingual children with language weaknesses. It remains to be clarified whether and under what circumstances target language vocabulary is more important for L2 than for L1 reading comprehension.…”
Section: Introductionmentioning
confidence: 96%
“…There is some evidence that poor reading comprehension skill is associated with syntactic difficulties in monolinguals (Mokhtari & Thompson, 2006 ; Muter, Hulme, Snowling, & Stevenson, 2004 ; Nation & Snowling, 2000 ), but research on the role of syntactic integration in L2 reading comprehension is sparse. When a measure of syntax is included in L2 research, it is often subsumed under a general language component (e.g., Babayiğit, 2015 ; Bowyer-Crane et al, 2016 ), or vocabulary is not controlled for in addition to syntax (e.g., Lesaux, Lipka, & Siegel, 2006 ). Proctor et al ( 2012 ) did investigate the unique contribution of syntax and found that syntax predicted English reading comprehension in monolingual English and Spanish–English bilinguals in second to fourth grade, after controlling for vocabulary breadth.…”
Section: Introductionmentioning
confidence: 99%
“…Since EAL children's English proficiency is highly predictive of their educational success and personal well-being (Strand & Demie, 2005;Strand & Hessel, 2018;Whiteside, Gooch, & Norbury, 2017), it is important to understand these challenges. EAL learners often lag behind monolinguals in reading comprehension and this is linked to relative deficits in vocabulary size and depth, but not reading fluency (Bowyer-Crane, Fricke, Schaefer, Lervåg, & Hulme, 2017;D'Angiulli, Siegel, & Serra, 2001;Hessel & Murphy, 2019;Lesaux, Rupp, & Siegel, 2007;Spätgens & Schoonen, 2018;Spencer & Wagner, 2017;Verhoeven, 2000). There is some evidence that EAL learners are less adept at comprehension monitoring, that is, with checking and regulating their understanding when reading figurative and multi-word phrases (Burgoyne, Whiteley, & Hutchinson, 2013;Kan & Murphy, in press).…”
Section: Comprehension Monitoring During Reading: An Eye-tracking Stumentioning
confidence: 99%